Anne of Green Gables - Montgomery, L. M. (Lucy Maud), 1874-1942. (Toronto ; New York : Bantam Books, 1984)
Summary : Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely, middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.
"A Bantam Starfire book."--Cover.
Keywords: Orphans -- Fiction; Foster home care -- Fiction; Country life -- Fiction; Prince Edward Island -- Fiction